Nursing professionals' biosafety in confronting COVID-19 - Mônica Alice Santos da Silva; Morgana Cristina Leôncio de Lima; Cynthia Angélica Ramos de Oliveira Dourado; Clarissa Mourão Pinho; Maria Sandra Andrade (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To investigate the nursing professionals' biosecurity in confronting COVID-19. Methods: This is a Survey type study. Nursing professionals were invited via messaging apps, using self-applied data collection forms. The sample selection (n=693) was non-probabilistic. A descriptive data analysis was conducted. Results: considering the biosafety aspects in facing COVID-19, 79.0% of the participants had not received training or considered it insufficient, 69.3% reported the lack of personal protective equipment during work, and 81.8% did not feel safe with the internal flux adaptations for handling COVID-19 cases. Conclusion: Continuous and effective nursing team training and personal protective equipment availability are necessary, as well as internal flow adjustments for attending suspected or confirmed cases.